Relative absorption of silicon from different formulations of dietary supplements: a pilot randomized, double-blind, crossover post-prandial study - N. Boqué (Nature Portfolio, 2021)
Abstract The purpose of the present study was to compare the relative absorption of a new powder presentation of silicon (Si) as orthosilicic acid with maltodextrin (Orgono Powder) compared to usual Si liquid presentations as orthosilicic acid with Equisetum arvense and Rosmarinus officinalis (G5 Siliplant) and orthosilicic acid with aloe vera (G7 Aloe). All dietary supplements were administered at the same Si oral dose (21.6 mg) in a randomized, double-blind, crossover post-prandial study conducted in 5 healthy men. Urine was collected at baseline and over the 6-h post-dose period in 2 separate 3-h collections for the analysis of Si concentration, which was conducted by inductively coupled plasma optical emission spectrometry as the gold standard method. No significant differences in total urinary Si excretion were found after the intake of these 3 dietary supplements; 34.6%, 32.4% and 27.2% of the ingested Si from G7 Aloe, G5 Siliplant and Orgono Powder, respectively, was excreted in urine over the 6-h follow-up period. The 3 different oral Si formulations tested, in powder and liquid presentations, provide highly bioavailable Si and present an equivalent relative absorption in healthy humans.